2018
DOI: 10.1007/s00128-018-2463-9
|View full text |Cite
|
Sign up to set email alerts
|

Metal Tolerance Capability of Helichrysum microphyllum Cambess. subsp. tyrrhenicum Bacch., Brullo & Giusso: A Candidate for Phytostabilization in Abandoned Mine Sites

Abstract: Sardinia was known as an important mine pole in Europe during his history. Still after decades from mine closure, 75.000.000 m 3 of mine waste, rich in heavy metals, were left abandoned causing a huge environmental legacy on the mine district area. Consequently, cost effective remediation is required. In this frame, phytoremediation is considered a feasible candidate. This research was focused on Helichrysum microphyllum subsp. tyrrhenicum, which is pioneer in xeric soils with low-functions, like mine tailings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 32 publications
6
23
0
Order By: Relevance
“…Zinc is the most abundant metal in the bulk soils (24,900 CP -32,700 OCP mg/kg), rhizospheres (26,300 CP -27,300 OCP mg/kg) and in the plant tissues (890 OCP -3290 CP mg/kg), followed by Pb (1240 OCP -5000 CP mg/kg in the soils, 1600 OCP -5030 CP mg/kg in the rhizospheres, and 50 OCP -1020 CP mg/kg in the plant tissues) and Cd (100 CP -340 OCP mg/kg in the soils, 170 CP -280 OCP mg/kg in the rhizospheres, and 13 OCP -31 OCP mg/kg in the plant tissues). It should be noted that metal contents detected in this work are of the same order of magnitude as in previous studies [39,41,46,91], in which relevant local variations due to heterogeneities of the mine tailings can be highlighted. [92] 1208 954 BCF, BAC, and TF (Table 3) were calculated to investigate the transfer of metals from geosphere to plant tissues and their translocation from the roots to the epigean organs.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Zinc is the most abundant metal in the bulk soils (24,900 CP -32,700 OCP mg/kg), rhizospheres (26,300 CP -27,300 OCP mg/kg) and in the plant tissues (890 OCP -3290 CP mg/kg), followed by Pb (1240 OCP -5000 CP mg/kg in the soils, 1600 OCP -5030 CP mg/kg in the rhizospheres, and 50 OCP -1020 CP mg/kg in the plant tissues) and Cd (100 CP -340 OCP mg/kg in the soils, 170 CP -280 OCP mg/kg in the rhizospheres, and 13 OCP -31 OCP mg/kg in the plant tissues). It should be noted that metal contents detected in this work are of the same order of magnitude as in previous studies [39,41,46,91], in which relevant local variations due to heterogeneities of the mine tailings can be highlighted. [92] 1208 954 BCF, BAC, and TF (Table 3) were calculated to investigate the transfer of metals from geosphere to plant tissues and their translocation from the roots to the epigean organs.…”
Section: Discussionsupporting
confidence: 82%
“…This structure was also detected by STXM ( Figure 6), also showing that Zn is mainly stored in the root epidermis. Moreover, the presence of Zn in the epidermis is consistent with previous study carried out on this plant species [39,46,47] that demonstrated its tolerance towards Zn via a metal exclusion strategy. In the rhizosphere, XAS analysis showed that Zn is mainly present as smithsonite, hydrozincite, and Zn sulfate, resulting from the oxidation of the primary Zn sulfides [110][111][112].…”
Section: Mineral Rim At the Root-rhizosphere Interface And Zn Chemicasupporting
confidence: 91%
See 2 more Smart Citations
“…Erica australis possesses the ability to uptake Cu, Cd and Pb via its roots without any sign of damage and suggest as a phytostabilizator species [123]. Bacchetta et al [13] indicated that Zn, Cd and Pb uptake was restricted largely in root tissue of Helichrysum microphyllum which is suitable for phytostabilization.…”
Section: Phytostabilizationmentioning
confidence: 99%